High inter-laboratory variability in the assessment of HER2-low breast cancer: a national registry study on 50,714 Danish patients - Kåre Nielsen; Michael Sode; Maj-Britt Jensen; Tobias Berg; Ann Knoop; Bent Ejlertsen; Anne-Vibeke Lænkholm (Breast Cancer Research, 2023)
Abstract Background Considering the recent advancements in the treatment of breast cancer with low expression of human epidermal growth factor receptor 2 (HER2), we aimed to examine inter-laboratory variability in the assessment of HER2-low breast cancer across all Danish pathology departments. Methods From the Danish Breast Cancer Group, we obtained data on all women diagnosed with primary invasive breast cancer in 2007–2019 who were subsequently assigned for curatively intended treatment. Results Of 50,714 patients, HER2 score and status were recorded for 48,382, among whom 59.2% belonged to the HER2-low group (score 1+ or 2+ without gene amplification), 26.8% had a HER2 score of 0, and 14.0% were HER2 positive. The proportion of HER2-low cases ranged from 46.3 to 71.8% among pathology departments (P < 0.0001) and from 49.3 to 65.6% over the years (P < 0.0001). In comparison, HER2 positivity rates ranged from 11.8 to 17.2% among departments (P < 0.0001) and from 12.6 to 15.7% over the years (P = 0.005). In the eight departments with the highest number of patients, variability in HER2-low cases increased from 2011 to 2019, although the same immunohistochemical assay was used. By multivariable logistic regression, the examining department was significantly related to both HER2 score 0 and HER2 positivity (P < 0.0001) but showed greater dispersion in odds ratios in the former case (range 0.25–1.41 vs. 0.84–1.27). Conclusions Our data showed high inter-laboratory variability in the assessment of HER2-low breast cancer. The findings cast doubt on whether the current test method for HER2 is robust and reliable enough to select HER2-low patients for HER2-targeted treatment in daily clinical practice.